Early and intermediate outcomes of patients who underwent gynaecological oncology surgery at Charlotte Maxeke Johannesburg Academic Hospital - Nchabeleng-Shibambu, Madithame Rachel (My University, 2021)
Aim: To investigate the immediate and intermediate outcomes of patients who underwent gynaecological oncology surgery at Charlotte Maxeke Johannesburg Academic Hospital in 2015 and 2016. The study focused on patients who experienced sustained complications during the open abdominal surgery. Objectives: To investigate the comorbidities associated with the complications in the women who underwent open abdominal surgery for confirmed gynaecological cancers. Method: This was a retrospective study. We checked the patients’ files to investigate the health status during operation and up to the 6 weeks postoperatively. The study was approved by the University of Witwatersrand Ethics Committee on Human Research. Results and Discussion: Two hundred and six (206) patients were operated for suspected gynaecological malignancies during the period. Ninety patients were confirmed to have malignancies. Thirty-one (31) patients had various complications while one died from haemorrhage. Conclusion: The finding that haemorrhage was the most common complication in open abdominal gynaecological oncology surgery was expected due to the extensiveness of the surgical procedure, the likelihoodof neo-vascularization, and tumour infiltration into vessels
A research report submitted to the Faculty of Hearth Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters in Medicine (MMed), 2021